2014
DOI: 10.3109/01443615.2014.896887
|View full text |Cite
|
Sign up to set email alerts
|

The fetal safety of cetirizine: An observational cohort study and meta-analysis

Abstract: Cetirizine, a second-generation antihistamine, is an active metabolite of hydroxyzine used in the treatment of allergies, but the data on fetal safety are inconclusive. Pregnant women who were counselled by the 'Motherisk Program' regarding cetirizine exposure were enrolled in a cohort study and compared with pregnant women counselled for non-teratogenic exposures. The objective was to measure the rate of adverse pregnancy outcomes. Subsequently, we also conducted a meta-analysis of cohort studies that examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The use of systemic medications should be minimized if possible. Pregnant (especially in the first trimester) and lactating women can receive second‐generation oral antihistamine treatment (no teratogenic effects have been described), and low concentrations of these drugs are secreted in breast milk …”
Section: Resultsmentioning
confidence: 99%
“…The use of systemic medications should be minimized if possible. Pregnant (especially in the first trimester) and lactating women can receive second‐generation oral antihistamine treatment (no teratogenic effects have been described), and low concentrations of these drugs are secreted in breast milk …”
Section: Resultsmentioning
confidence: 99%
“…Cetirizine was not associated with increase rate of major malformations or increase teratogenic risk. 585 A study using the UCB Pharma Patient Safety Database up to February 2015 reaffirmed the safety of cetirizine in pregnancy. 586 A 2013 study using data from a multicenter case-control surveillance program of birth defects in North America did not support previously posited associations between antihistamines, notably diphenhydramine, loratadine, and chlorpheniramine, and major congenital anomalies.…”
Section: Rhinitis In Pregnancymentioning
confidence: 97%
“…Similarly, data from the Swedish Medical Birth Registry, which included 917 women who had taken CTZ during their pregnancy, showed no association with malformations or adverse delivery outcomes, compared to the general population (K€ all en 2002). A cohort study involving 78 pregnant women exposed to CTZ in the first, and 56 in the second or third trimester demonstrated no increased risk of major malformations or spontaneous abortions when CTZ was taken during organogenesis, compared to the control group of women taking non-teratogenic agents (Etwel et al 2014). Similarly, a meta-analysis of 10 studies involving 1293 pregnant women reported no 8 (100.0) 0 0 0 0 Third (n ¼ 2) 2 (100.0) 0 0 0 0 Unknown (n ¼ 5) 5 (100.0) 0 0 0 0 Trimesters exposed n (%) 1 only (n ¼ 8) 4 (50.0) 3 (37.5) 1 (12.5) 0 0 2 only (n ¼ 3)…”
Section: Discussionmentioning
confidence: 99%
“…Prospective reports (n ¼ 41) n (%) increased risk of major malformations or other adverse foetal outcomes following hydroxyzine or CTZ exposure, compared to the unexposed controls (Etwel et al 2014). The limitations of the analysis include that the UCB Pharma Patient Safety Database is a surveillance reporting tool for adverse events, rather than an analysis tool, and the data collection process is tailored to pharmacovigilance purposes.…”
Section: Live Birth Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation